Impact of development finance institutions on sustainable development: An essay series - Samantha Attridge; Dirk Willem te Velde; Søren Peter Andreasen (Overseas Development Institute (ODI), 2019)
Development finance institutions (DFIs) have a positive role to play in supporting economic growth and job creation through the mobilisation of private investment in developing countries. There is growing evidence of their contributions towards the Sustainable Developments Goals (SDGs), in particular SDG 7 (ensuring access to affordable, reliable, sustainable and modern energy for all), SDG 8 (promoting sustained, inclusive and sustainable economic growth, full and productive employment and decent work for all) and SDG 13 (taking urgent action to combat climate change and its impacts). This essay series, co-produced with the European Development Finance Institutions, brings together an array of perspectives from academics, researchers, practitioners and civil society, to assess the role of DFIs in attaining the SDGs. The essays examine the contribution of DFIs to job creation and decent work, climate change and access to clean energy, and also argue that there is potential to harmonise impact measuring and reporting among DFIs.
Keywords: 330